Pedagogiczne emergencje w 1993 roku. Cienie przeszłości czy szanse teraźniejszości? - Kwieciński , Zbigniew (Studia Edukacyjne, 2018)
ThThe 25th anniversary of the Department of Educational Studies is an inspiration for the author to return to the pedagogical events of 1993. The article by Mikołaj Kozakiewicz published this year contains warnings that the chances of Polish education after a major educational change after 1989 (democracy, pluralism, europeization) are lost, and anticipates their reversal. centralism, authoritarianism, ideological monism, the closing of Poland to Europe are coming back. These anxieties also appeared at the First National Pedagogical Congress in Rembertów in 1993, although the prevailing concern was whether pedagogy as science kept up with the great changes. At the same time, a new formation and a generation of academic pedagogues emerged at this Congress, undertaking new challenges of this time. Unfortunately, sociologists and intercultural psychologists studies have shown that the chances of great change have been educationally wasted, which is manifested in the low culture of everyday life of Poles and in the persistence of Polish perennial, negative social stereotypes. The author, however, finds and presents reasons for the pedagogy of possibilities, supporting the development of people to autonomy and humanity.e 25th anniversary of the Department of Educational Studies is an inspiration for the author to return to the pedagogical events of 1993. The article by Mikołaj Kozakiewicz published this year contains warnings that the chances of Polish education after a major educational change after 1989 (democracy, pluralism, europeization) are lost, and anticipates their reversal. centralism, authoritarianism, ideological monism, the closing of Poland to Europe are coming back. These anxieties also appeared at the First National Pedagogical Congress in Rembertów in 1993, although the prevailing concern was whether pedagogy as science kept up with the great changes. At the same time, a new formation and a generation of academic pedagogues emerged at this Congress, undertaking new challenges of this time. Unfortunately, sociologists and intercultural psychologists studies have shown that the chances of great change have been educationally wasted, which is manifested in the low culture of everyday life of Poles and in the persistence of Polish perennial, negative social stereotypes. The author, however, finds and presents reasons for the pedagogy of possibilities, supporting the development of people to autonomy and humanity.